(untitled) (OpenFOAM® Journal, 2022)
Separated Vortex Ring above a Three-Dimensional Porous Disc Chandan Bose School of Engineering, Institute for Energy Systems, The University of Edinburgh, Edinburgh, Scotland, United Kingdom. chandan.bose@ed.ac.uk, http://www.chandanbose.com Ignazio Maria Viola School of Engineering, Institute for Energy Systems, The University of Edinburgh, Edinburgh, Scotland, United Kingdom. i.m.viola@ed.ac.uk, https://voilab.eng.ed.ac.uk References Chandan Bose and Ignazio Maria Viola (2022). Gust Response of Falling Porous Bodies, to be submitted in Journal of Fluid Mechanics.